The Effectiveness of Fresh Technique in Writing Descriptive Essay at SMPN 12 Gorontalo - Siti Mutiyah Tolinggi; Muziatun M; Sri Agriyanti Mestari (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Writing is one of the skills that must be possessed by students when learning English. It is one way of expressing ideas, feelings, thoughts, even arguments and knowledge into a piece of paper. Descriptive text is a text which purpose is to describe someone, a place, or something.FRESH Technique is a teaching technique can help student writing descriptive text. The aim of this study was to find out the significant difference in writing achievement before and after students taught using the FRESH technique in writing descriptive Essay. In conducting the study, The method in this study is a quantitative method. A-pre experimental was employed as research design conducted into one group. The sample of this study is the seventh-grade in class VII-3 The researcher took twenty five students as the sample.The instrument for collecting the data using T-test that included a pre-test and post-test. The data analysis using T-test and analyzed by using SPSS version 25.The research found that the students had an average developmental in writing descriptive essay of 10,44 on pre test and 15,4 on the post-test. The students writing development is 37,82%. This is supported by the larger t-test value showed that the t-test 29,632 > t-table 2,807. The result indicates that,the null hyphothesis (H0) was rejected while the alternative hyphothesis (Ha) was accepted it means that FRESH Technique can effective increased student’s writing in descriptive essay.